Engineering Iron Oxide Nanoparticles for Clinical Settings. (9th July 2014) - Cortajarena, Aitziber L.; Ortega, Daniel; Ocampo, Sandra M.; Gonzalez-García, Alberto; Couleaud, Pierre; Miranda, Rodolfo; Belda-Iniesta, Cristobal; Ayuso-Sacido, Angel
Iron oxide nanoparticles (IONPs) occupy a privileged position among magnetic nanomaterials with potential applications in medicine and biology. They have been widely used in preclinical experiments for imaging contrast enhancement, magnetic resonance, immunoassays, cell tracking, tissue repair, magnetic hyperthermia and drug delivery. Despite these promising results, their successful translation into a clinical setting is strongly dependent upon their physicochemical properties, toxicity and functionalization possibilities. Currently, IONPs-based medical applications are limited to the use of non-functionalized IONPs smaller than 100 nm, with overall narrow particle size distribution, so that the particles have uniform physical and chemical properties. However, the main entry of IONPs into the scene of medical application will surely arise from their functionalization possibilities that will provide them with the capacity to target specific cells within the body, and hence to play a role in the development of specific therapies. In this review, we offer an overview of their basic physicochemical design parameters, giving an account of the progress made in their functionalization and current clinical applications. We place special emphasis on past and present clinical trials.